Francisco Dias Gomes. Duas tragédias clássicas: Ifigénia e Electra - José Augusto Cardoso Bernardes (Dramaturgia, 2020)
This book includes an introduction about the reception of ancient Greek theatre among the members of the Portuguese Arcadia Lusitana in general, to contextualize the production of Francisco Dias Gomes. It is followed by the edition of two tragedies - Iphigeneia and Electra -, in both cases with a large introduction, mainly foccused on the relation between the two plays from the 18th century and their ancient models.